Flow structures over mesophotic coral ecosystems in the eastern Gulf of Mexico. (16th December 2020) - Valle-Levinson, Arnoldo; Kourafalou, Villy H.; Smith, Ryan H.; Androulidakis, Yannis
Abstract: Simultaneous time series of current velocity profiles are used to characterize flow structures over intermediate-depth coral ecosystems in the eastern Gulf of Mexico. Understanding of temporal variability and spatial coherence in flow is necessary to establish connectivity among these ecosystems. Time series were collected at Pulley Ridge (the westernmost site), Northern Dry Tortugas, and Southern Dry Tortugas. Overlapping data spanned the period from March 22, 2013 to June 20, 2015. The strongest currents were approximately 1 m s -1 southeastward at Pulley Ridge. Subtidal velocities from the three sites were decomposed into real-vector, concatenated empirical orthogonal functions (EOFs). Results from EOFs indicated that Mode 1, which explained 63% of the subtidal variance, was roughly in the same direction at each of the three sites. Mode 1 directionality indicated potential interconnectivity between Pulley Ridge and Southern Dry Tortugas, and between Northern Dry Tortugas and Pulley Ridge. Mode 1 also suggested limited to no connectivity between the two Dry Tortugas sites as the flows over the two sites were parallel. Mode 2 explained close to 24% of the variance and showed incoherence among the three sites. Wavelet analysis of EOF coefficients indicated dominance of >1 week variability in this region. Flow variability may be associated with wind forcing and Loop Current variability as confirmed by satellite altimetry. Wind forcing caused part of the intra-monthly (<1 month) periodicity in flows. Sea level in the area of the Loop Current, as derived from EOF application on altimetry data during the period of velocity measurements, was related to Mode 1 of the currents at sub-monthly (>1 month) periods. The relationship was more robust, but inverse, when comparing sea level off the northwestern coast of Cuba to the Mode 1 of the currents. These results characterize physical connectivity among South Florida coral ecosystems and have biophysical implications for coral fish populations. Highlights: Flow profiles at 3 sites over mesophotic corals of the SW Florida Shelf were influenced by a looping western boundary current during ~2.5 years. Flow profiles had most of their variance represented by nearly depth-independent flows moving roughly in the same direction at the 3 sites sampled. The Loop Current affected flows at sub-monthly periodicities (>1 month) but winds influenced flows at intra-monthly periodicities (<1 month).